2017
DOI: 10.1016/j.celrep.2017.07.034
|View full text |Cite
|
Sign up to set email alerts
|

A Soluble Fluorescent Binding Assay Reveals PIP2 Antagonism of TREK-1 Channels

Abstract: SUMMARY Lipid regulation of ion channels by low-abundance signaling lipids phosphatidylinositol 4,5-bisphosphate (PIP2) and phosphatidic acid (PA) has emerged as a central cellular mechanism for controlling ion channels and the excitability of nerves. A lack of robust assays suitable for facile detection of a lipid bound to a channel has hampered the probing of the lipid binding sites and measuring the pharmacology of putative lipid agonists for ion channels. Here, we show a fluorescent PIP2 competition assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
104
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(114 citation statements)
references
References 40 publications
9
104
1
Order By: Relevance
“…2H) at 100 mV with 270 nM Ca 2+ . This falls within the range reported for PI(4,5)P2 binding to other ion channels (0.12 µM to 4.6 µM, (47)(48)(49)). At -100 mV, inward currents were more sensitive to diC8-PI(4,5)P2 with EC50 < 0.1 µM ( Fig.…”
Section: The Effect Of Pi(45)p2 Is Dependent On Voltage and Ca 2+supporting
confidence: 88%
“…2H) at 100 mV with 270 nM Ca 2+ . This falls within the range reported for PI(4,5)P2 binding to other ion channels (0.12 µM to 4.6 µM, (47)(48)(49)). At -100 mV, inward currents were more sensitive to diC8-PI(4,5)P2 with EC50 < 0.1 µM ( Fig.…”
Section: The Effect Of Pi(45)p2 Is Dependent On Voltage and Ca 2+supporting
confidence: 88%
“…2c) failed to respond and suggests that PLD2 localization is a significant contributor to TREK-1 activation. Since the PLD-TREK-1 complex was shown above to translocate to PIP2 domains and PIP2 is a TREK-1 antagonist 44 , it is likely that without co-localization the local concentration of PA does not reach sufficient levels to compete with PIP2 binding 11 . It may be possible if PLD2 dependent PA production could reach activating concentration if the membrane and or cytoskeleton were sufficiently disrupted.…”
Section: Discussionmentioning
confidence: 99%
“…2, 3e). Since PIP2 directly antagonizes TREK-1 44,45 , the localization of TREK-1 to PIP2 before and after shear (Fig 3c,e) explains the strong inhibition of TREK-1 by xPLD2 ( Fig. 2b-c).…”
Section: The Trek-1 Force Transduction Pathwaymentioning
confidence: 92%
See 1 more Smart Citation
“…PLD is known to be sensitive to its localization to lipid domains 5 and recent research has shown that anesthetics have a significant effect on the organization of these domains 2,19,20 . PLD and its activating lipid PA have also been shown to directly control the activity of the mammalian potassium channel TREK-1, a hyperpolarizing channel 7,21 . While it is unknown what channels with which the fly ortholog of PLD are associated, recent experiments have shown that it too is likely helping to regulate a hyperpolarizing channel like TREK-1.…”
Section: Discussionmentioning
confidence: 99%